2010
DOI: 10.1016/j.molstruc.2010.03.081
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectra of methyl isocyanate isolated in Ar, Xe and N2 matrices

Abstract: The infrared spectra of methyl isocyanate monomer isolated in cryogenic argon, xenon and nitrogen matrices were studied. Interpretation of the experimental results was supported by harmonic and anharmonic calculations carried out at the DFT, MP2 and CCSD levels of approximation. Spectral indicators of the molecule structural flexibility were examined, the most striking of these being the multiplet structure of the most intense infrared band due to the antisymmetric stretching vibration of the N@C@O group. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 62 publications
5
24
0
Order By: Relevance
“…Also a clear red shift of about 10 cm −1 of the two features is seen between the sample of 12 CH 4 and 13 CH 4 , moving transitions at 2322 and 2303 cm −1 to 2313 and 2294 cm −1 . These spectroscopic features are therefore the result of a product formed in the reaction between methane and isocyanic acid, and, since they are found close to known CH 3 NCO features (given by Sullivan et al (1994) and Reva et al (2010)), are plausibly identified with methyl isocyanate. Another feature is seen in the wing of the HNCO peak around 2235 cm −1 , which does not clearly shift with methane isotopologues.…”
Section: Set-up and Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…Also a clear red shift of about 10 cm −1 of the two features is seen between the sample of 12 CH 4 and 13 CH 4 , moving transitions at 2322 and 2303 cm −1 to 2313 and 2294 cm −1 . These spectroscopic features are therefore the result of a product formed in the reaction between methane and isocyanic acid, and, since they are found close to known CH 3 NCO features (given by Sullivan et al (1994) and Reva et al (2010)), are plausibly identified with methyl isocyanate. Another feature is seen in the wing of the HNCO peak around 2235 cm −1 , which does not clearly shift with methane isotopologues.…”
Section: Set-up and Methodssupporting
confidence: 71%
“…Sullivan et al (1994) lists these at 2320, 2280, 2270, 2240 and 2228 cm −1 , with 2280 cm −1 being the strongest band. Zhou & Durig (2009) positioned all bands around 2300 cm −1 and Reva et al (2010) puts the band for methyl isocyanate in a nitrogen matrix at 2334.7, 2307.9, 2288.9, 2265.2 and 2259.7 cm −1 , finding the strongest transition at 2288.9 cm −1 . The region around these bands is used to monitor CH 3 NCO formation in the ice.…”
Section: Set-up and Methodsmentioning
confidence: 99%
“…The band broadening in this case is usually associated with vibrations along shallow potential energy profiles that result in large amplitude vibrations. 42,59,60 Analysis of Figure 1 shows that conformer 1ccc has a very shallow potential energy profile for internal rotation along the CCC=O and, especially, NCCC dihedral angles. The carboxylic group in 1ccc is slightly distorted from the tetrazole ring plane (Figure 4), and this conformer may undergo large variations of geometry, keeping a low internal energy (Figure 1, top).…”
Section: Experimental Infrared Spectrum Of Matrix-isolated Taamentioning
confidence: 99%
“…23 The infrared and Raman spectra of the gas and solid phases were measured by Sullivan et al 24 in the 3200-20 cm −1 and 3200-10 cm −1 regions, respectively. Reva et al 25 recorded the infrared spectra of methyl isocyanate isolated in Ar, Xe, and N 2 matrices.…”
Section: Introductionmentioning
confidence: 99%